2009
DOI: 10.2174/1874848100902010077
|View full text |Cite
|
Sign up to set email alerts
|

Nematicidal Activity of Plant Extracts Against the Root-Knot Nematode, Meloidogyne incognita

Abstract: Nematicidal activity of extracts from plants was assayed against Meloidogyne incognita. In laboratory assays extracts from tobacco (Nicotiana tabacum L), clove (Syzygium aromaticum L), betelvine (Piper betle L), and sweet flag (Acorus calamus L) were most effective in killing the nematode, with an EC 50 that was 5-10 times lower than the EC 50 of the synthetic pesticides chlorpyrifos, carbosulfan and deltamethrin. The shapes of the dead nematodes differed in a characteristic way, and groups of pesticides and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 35 publications
(28 reference statements)
4
29
0
11
Order By: Relevance
“…bevanii), rosemary (Rosmarinus officinalis), fennel (Foeniculum vulgare) and Phytophthora infestans (Soylu et al, 2006). The nematicidal activity of some plant preparations, including the activity of essential oils against Meloidogyne spp., has been demonstrated (Oka, 2000;Chitwood, 2002;Zasada et al, 2006;Wiratno et al, 2009). Meyer et al (2006) reported that extracts of Plantago lanceolata and P. rugelii were toxic to M. incognita eggs and J2, with the P. lanceolata extract tending to have the most activity.…”
Section: Resultsmentioning
confidence: 99%
“…bevanii), rosemary (Rosmarinus officinalis), fennel (Foeniculum vulgare) and Phytophthora infestans (Soylu et al, 2006). The nematicidal activity of some plant preparations, including the activity of essential oils against Meloidogyne spp., has been demonstrated (Oka, 2000;Chitwood, 2002;Zasada et al, 2006;Wiratno et al, 2009). Meyer et al (2006) reported that extracts of Plantago lanceolata and P. rugelii were toxic to M. incognita eggs and J2, with the P. lanceolata extract tending to have the most activity.…”
Section: Resultsmentioning
confidence: 99%
“…Pada tahun 1800, bubuk tanaman pirethrum digunakan untuk mengendalikan kutu daun (Chan Bacab dan Pena Rodriguez 2001; Biebel et al 2003). Penggunaan pestisida nabati selain dapat mengurangi pencemaran lingkungan, juga lebih murah dibandingkan dengan pestisida kimia (Zhu et al 2001;Auger et al 2004;Wiratno et al 2009;Wiratno et al 2011).…”
Section: Potensi Tumbuhan Sebagai Sumber Insektisida Nabatiunclassified
“…Jenis-jenis tanaman yang telah diketahui efektif mengendalikan hama pertanian antara lain adalah pyrethrum untuk mengendalikan hama gudang (Biebel et al 2003;Athanassiou dan Kavallieratos 2005;Vayias et al 2006), jeringo untuk mengendalikan Lasioderma serricorne, Sitophilus oryzae, dan Callosobruchus chinensis (Kim et al 2003a;2003b), tembakau untuk mengendalikan hama polong kacang tunggak dan Callosobruchus maculatus (Opolot et al 2006), cengkih untuk mengendalikan Dermanyssus gallinae, Ixodes ricinus, dan Meloidogyne incognita (Thorsell et al 2006;Wiratno et al 2009); lada sebagai antimikroba (Pradhan et al 1999), mimba untuk mengendalikan Cnaphalocrocis medinalis (Nathan et al 2006), serai wangi sebagai penolak nyamuk (Oyedele et al 2002) dan pengendali Dasynus piperis (Rohimatun dan Laba 2013) dan Conophomorpa cramerella (Willis et al 2013), sirih untuk mengendalikan Chrysomya bezziana (Wardhana et al 2007), akar tuba untuk menghambat enzim pernapasan (Hien et al 2003), jambu mete untuk mengendalikan hama gudang (Oparaeke dan Bunmi 2006), akar wangi sebagai pengendali rayap (Zhu et al 2001), serta tanaman daun encok.…”
Section: Active Ingredient Of Botanical Pesticides Is Still Not Yet Uunclassified